Efeitos do treino em esteira na marcha com dupla tarefa de indivíduos com doença de Parkinson: ensaio clínico controlado randomizado - Sousa, Angelica Vieira Cavalcanti de (2012)
Background: The gait automaticity loss difficults realization of concurrent activities - Dual Task (DT). In these situations, individuals with Parkinson`s disease (PD) show a significant reduction in gait velocity and stride length, as strides variability and asymmetry increased, factors predisposing to falls. However, recent studies have shown that training involving DT may cause subsequent improvements in gait variables with DT in individuals with PD. The treadmill use was adopted by this study, by promoting greater regularity in step and enhance training. Objective:To investigate immediate effects of gait training associated with cognitive tasks on gait in individuals with PD. Methods: Twenty-two volunteers were randomly divided into two groups: control group (n = 11), who performed gait training on a treadmill for 20 minutes, and the experimental group (n = 11), who performed treadmill gait training for 20 minutes associated with cognitive tasks of verbal fluency, memory, and spatial planning. Participants were evaluated in phase on of antiparkinsonian medication as the demographic, clinical and anthropometric (identification form), cognitive status (Montreal Cognitive Assessment - MoCA), executive function (Frontal Assessment Battery), level of physical disability (Hoehn and Yahr Modified), motor and functional status (Unified Rating Scale for Parkinson`s Disease - UPDRS), and kinematics (Qualisys Motion Capture System). Results: There were not differences between groups, but both showed improvement after the intervention. The control group had an increase in velocity (p = 0.008), stride length (p = 0.04), step length (p = 0.02) and decreased double support time(p = 0.03). The experimental group showed an increase in speed (p = 0.002), stride length (p = 0.008), step length (p = 0.02) and cadence (p = 0.01), as well as a decrease in the width stride (p = 0.001) and total support time (p = 0.02). As the angular variables, the experimental group had a significant increase in the initial contact angle of ankle (p = 0.01). Conclusion: The gait training combined with cognitive activities didn`t provide significant improvements in gait variables with DT, but this study was the first to demonstrate that gait training on treadmill as simple task minimized the negative interference of DT in PD